VD_FINDINFO HC / 2013 / 134 vom 26. Februar 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE | 109 al. 1 CPC (CH), 122 al. 1 let. a CPC (CH), 123 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)